On compensation for personal injury cases. - Goh, Geok Hoon. (2013)
Law has always been a confusing subject for many of us. When we first took on the topic of “On Compensation for Personal Injury Cases” for our Applied Research Project, we were appalled by the vast numbers of technical terms used. Hence, for a better understanding by a layperson, we summarised the major concepts and principles so as to provide a simpler explanation of the topic.